Effectiveness of Peer Group Guidance With Poetry Therapy Techniques and Sociodrama Techniques to Improve Self Disclosure - Nikmah, Rif’atun; Puji Sugiarto, Dwi Yuwono; Awalya, Awalya (Jurnal Bimbingan Konseling, 2022)
Self-disclosure is an act or behavior which shows a state to express information covering thoughts, feelings, and actions to strengthen a relationship. This research was focused on describing the effectiveness of self-disclosure level of students in SMP Takhasus Al-Quran Rafirna, Tersono, Batang Regency. 24 students were involved in experimental research which adopted randomized pretest posttest comparison group design. Based on the results of Wilcoson and Mann Whitney tests, the group of poetry art therapy and sociodrama techniques gained effective results in promoting students’ self-disclosure. Here, the peer group counseling with sociodrama technique is more recommended to improve students’ self-disclosure.